Person-Organization Fit in Teacher Recruitment: Fostering Affective Commitment and Talent Retention in Schools - Wafi Bahrul Ilmi; Nur Ainayatul Karimah; Fahmi Hasbi Arrosyad; Fajar Zainulloh; Siti Aimah (International Journal of Science and Environment (IJSE), 2026)
This study aims to conduct an in-depth analysis of how the implementation of person-organization fit in the teacher recruitment process shapes affective commitment and supports talent retention. This study employs a qualitative approach with a case study design to analyze the implementation of person-organization fit in teacher recruitment and its role in shaping affective commitment and talent retention at Madrasah Aliyyah Salafiyah Syafi’iyah Sukorejo Bangorejo Banyuwangi. The research was conducted over one month, involving four informants selected through purposive sampling. Data were collected through in-depth interviews, non-participant observation, and documentation, then analyzed using the interactive model by Miles, Huberman, and Saldaña through the stages of open coding, axial coding, and selective coding. Data credibility was ensured through source triangulation, methodological triangulation, and member checking. The results of this study indicate that the implementation of person-organization fit in teacher recruitment is a crucial strategy for fostering affective commitment, retaining talent, and ensuring the sustainability of human resource management at Madrasah Aliyyah Salafiyah Syafi’iyah Sukorejo Bangorejo, Banyuwangi. Value alignment between teachers and the organization from the recruitment stage accelerates adaptation, strengthens emotional attachment, and enhances participation in institutional development. Theoretically, this study expands the perspective of Person-Organization Fit Theory by positioning it as a strategic mechanism that integrates recruitment, affective commitment, and talent management. The research implications underscore the importance of integrating value alignment into the teacher recruitment and development processes to support the sustainability of value-based educational organizations.